The Structure and Signaling Mechanisms of Type 1 Cytokine Receptors: A Brief Overview - Esen, Ihsan (Turkish Soc Immunology, 2015)
Cytokines, the secreted messenger molecules, act on their target cells by binding specific membrane receptors. Many cell functions are regulated by members of cytokine receptors mediated intracellular signaling mechanisms. The classification of cytokine receptors is based on structural homologies of extracellular cytokine-binding domains and shared intracellular signaling mechanisms. A simple classification of cytokine receptors contains type 1 cytokine receptors, type 2 cytokine receptors, tumor necrosis factor receptor family, interleukin 1 receptor family, and seven transmembrane G-protein-coupled receptors. This article focuses on the structure and associated signaling pathways of type 1 cytokine receptors.
Keywords: Cytokines; receptors; type 1 cytokine receptors